Ilmu nujum: aspek pernujuman dan pancaran kecendekiaan masyarakat - Haron Daud, (Universiti Kebangsaan Malaysia, 2010)
Ilmu nujum or astrology is the knowledge to predict something else. This prediction mostly bases on planet, especially the stars on the universes. The objectives of this article are to show the type of predictions in the Malay society which are wroth in the Malay manuscripts. There are like to predict the person either he/she has bad or good luck; to predict the lucky or unlucky for husband and wife; to predict the dream, and to predict what someone doing either good or bad base on dragon setting, and another objective is to show that the Malay author whom wroth that manuscript are brilliant